2013
DOI: 10.1111/pace.12262
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Midterm Performance of Active‐Fixation Leads Using Current of Injury

Abstract: Midterm performance of active-fixation leads is predictable using COI recorded at the time of lead implantation. A ST-segment elevation ≥2.0 mV in the atrial leads and ≥10.0 mV in the ventricular leads are recommended to improve the lead performance at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
(18 reference statements)
0
9
1
1
Order By: Relevance
“…Fixation of leads into myocardial tissue during cardiac device implantation results in acute tissue injury also known as current of injury (COI) and is recognized by an elevation of the ST‐segment compared with baseline and an increase in the duration of the intracardiac electrogram (EGM) 1 . Several studies have demonstrated that the presence of a COI is associated with better acute performance and long‐term stability with active fixation leads 1–6 . Vijayaraman et al 3 reported the presence of His bundle COI with leads implanted at the His bundle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixation of leads into myocardial tissue during cardiac device implantation results in acute tissue injury also known as current of injury (COI) and is recognized by an elevation of the ST‐segment compared with baseline and an increase in the duration of the intracardiac electrogram (EGM) 1 . Several studies have demonstrated that the presence of a COI is associated with better acute performance and long‐term stability with active fixation leads 1–6 . Vijayaraman et al 3 reported the presence of His bundle COI with leads implanted at the His bundle.…”
Section: Introductionmentioning
confidence: 99%
“…performance and long-term stability with active fixation leads. [1][2][3][4][5][6] Vijayaraman et al 3 reported the presence of His bundle COI with leads implanted at the His bundle. His bundle COI was noted in 37% of cases undergoing His bundle pacing (HBP) and was associated with a low pacing threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, patients have accepted ICDs as life sustaining technology, and they are widely used worldwide ( 6 ). The first ICD was used in 1980 ( 7 ), and in Iran, the history of this device goes back to 1995 ( 8 ). Although an ICD is much more effective than other treatments in controlling dysrhythmias and heart diseases ( 9 ), living with an ICD is accompanied with challenges for both the patients and their families ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Haghjoo et al. reported that the mid‐term performance of active fixation leads could be estimated by the ST‐segment elevation at the time of fixation . Both atrial and ventricle leads with good performance exhibited a higher ST‐segment elevation at the time of fixation.…”
Section: Discussionmentioning
confidence: 99%